Calpain-mediated tau fragmentation is altered in Alzheimer's disease progression. Issue 1 (December 2018) - Chen, Hsu-Hsin; Liu, Peter; Auger, Paul; Lee, Seung-Hye; Adolfsson, Oskar; Rey-Bellet, Lorianne; Lafrance-Vanasse, Julien; Friedman, Brad; Pihlgren, Maria; Muhs, Andreas; Pfeifer, Andrea; Ernst, James; et al.
Abstract The aggregation of intracellular tau protein is a major hallmark of Alzheimer's disease (AD). The extent and the stereotypical spread of tau pathology in the AD brain are correlated with cognitive decline during disease progression. Here we present an in-depth analysis of endogenous tau fragmentation in a well-characterized cohort of AD and age-matched control subjects. Using protein mass spectrometry and Edman degradation to interrogate endogenous tau fragments in the human brain, we identified two novel proteolytic sites, G323 and G326, as major tau cleavage events in both normal and AD cortex. These sites are located within the sequence recently identified as the structural core of tau protofilaments, suggesting an inhibitory mechanism of fibril formation. In contrast, a different set of novel cleavages showed a distinct increase in late stage AD. These disease-associated sites are located outside of the protofilament core sequence. We demonstrate that calpain 1 specifically cleaves at both the normal and diseased sitesin vitro, and the site selection is conformation-dependent. Monomeric tau is predominantly cleaved at G323/G326 (normal sites), whereas oligomerization increases cleavages at the late-AD-associated sites. The fragmentation patterns specific to disease and healthy states suggest novel regulatory mechanisms of tau aggregation in the human brain.